The Enduring Repercussions of Colonization on Modern Artifact Repatriation in West Africa - Ona Carlisle (UNC Test Journal, 2025)
The colonial era led to the extensive removal of cultural artifacts from Africa, with many of these objects now residing in Western museums. Over the last century, there has been an increasing global recognition of the importance of repatriating these artworks to their countries of origin. Repatriation is particularly crucial for African countries, where a majority of the population is under twenty, and oral traditions passed down by elders are vital for preserving knowledge of cultural heritage. This paper explores the impact of colonization on repatriation debates, highlighting the role of Operation Legacy and the creation of artificial borders during colonization that have further complicated the process. The colonial borders established during colonization have led to multiple ownership and boundary disputes that further hinder repatriation efforts. Operation Legacy was a covert British operation initiated during decolonization in Africa, which resulted in the removal, destruction, and hiding of thousands of official African records, documents, and artifacts in former British colonies. This destruction of African history was used as a form of narrative control for the British to rewrite the history of colonization in their favor. While exceptions for looted artifacts have been made in response to laws that restrict repatriation in countries like Britain and France, looted African artifacts could not be included due to time period limitations. Through examining the legal struggles, preservation concerns, and ownership issues regarding the return of the Benin Bronzes, this study will provide insight into the multifaceted nature of returning art looted during colonization.